Fractional CO2 laser for the treatment of sclerodermatous cGVHD. (2nd January 2020) - Labadie, Jessica G.; Kosche, Cory; Kyllo, Rachel; Johnson, Tyler; Shumaker, Peter R.; Alam, Murad; Choi, Jennifer N.
ABSTRACT: Sclerodermatous graft versus host disease (sclGVHD) is a debilitating complication of hematopoietic stem cell transplant and is characterized by skin thickening and fibrosis that can result in severe contractures. While immunosuppressive therapy remains a mainstay of treatment, the disease course often progresses and, in severe cases, renders patients immobile and wheelchair-bound. Lasers that can target sclerotic lesions to improve tissue pliability and restore range of motion are a promising potential treatment for sclGVHD. Fractional CO2 lasers promote selective collagen remodeling by creating microcolumns of thermal injury that stimulate a wound healing response. Here, we present 2 patients with sclGVHD who underwent treatment with fractional ablative CO2 laser. In this pilot case series demonstrating the novel use of CO2 laser for severe, refractory sclGVHD, two patients were treated with fractional ablative CO2 laser to a focal area of sclerosis. One patient also received clobetasol ointment under occlusion in between treatments. Both patients reported marked subjective improvement in pain and mobility. Objective measurements were recorded for patient 2 who gained roughly 10 degrees of extension and 2 degrees of flexion, as well as a 10% reduction in skin thickness in the treated area. CO2 laser therapy with or without clobetasol ointment under occlusion is a promising treatment modality for sclGVHD.